Simultaneous organic and nitrogen removal using anoxic - aerobic membrane bioreactor - Birima, Ahmed Hussein; Megat Mohd Noor, Megat Johari; Mohammed, Thamer Ahmed; Muyibi, Suleyman Aremu; Idris, Azni (Federation of Engineering Institutions of Islamic Countries, 2006)
In this paper, anoxic - aerobic membrane bioreactor was constructed and used to investigate the possibility of simultaneous removal of organics and nitrogen. The membrane module was submerged in the aerobic zone of the bioreactor and was operated under an intermittent suction mode. The module was aerated from beneath the microfiltration module to provide the cross flow effect and the oxygen requirement for the biological process. The aeration around the membrane module and the intermittent mode served as the cleaning mechanism for the membrane; this resulted in an operation of the reactor at the flux of 2.7 – 5.4 L m-2 h-1 for 180 days. Hydraulic retention time was ranged between 14.9 to 22.3 hours. MLSS of over 12000 mg/l was reached. The mixed liquor suspended solids (MLSS) internal recycling ratio (between the aerated compartment and anoxic compartment) was maintained at 300 % influent flow rate. The average efficiency of the chemical oxygen demand (COD), removal was 99.3 % for an average COD of 418 mg/l. 99.3 % of influent ammonia was converted to oxidized nitrogen. Permeate inorganic nitrogen reduction was 65.3 %.